2012
DOI: 10.1002/jbm.a.34016
|View full text |Cite
|
Sign up to set email alerts
|

In situ formation of porous space maintainers in a composite tissue defect

Abstract: Reconstruction of composite defects involving bone and soft tissue presents a significant clinical challenge. In the craniofacial complex, reconstruction of the soft and hard tissues is critical for both functional and aesthetic outcomes. Constructs for space maintenance provide a template for soft tissue regeneration, priming the wound bed for a definitive repair of the bone tissue with greater success. However, materials used clinically for space maintenance are subject to poor soft tissue integration, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 33 publications
(56 reference statements)
0
21
0
Order By: Relevance
“…The primary differences in formulation between the samples in this study and the samples used in previous studies are the use of gelatin as a porogen and the delivery of antibiotics. [9,10] These dehiscences could therefore be due to the presence of gelatin, colistin, or their combination. Although gelatin cannot be excluded as a cause of dehiscence, it is perhaps a less likely culprit as previous studies have not shown dehiscence when gelatin is implanted in the oral and maxillofacial region, though these studies are not extensive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary differences in formulation between the samples in this study and the samples used in previous studies are the use of gelatin as a porogen and the delivery of antibiotics. [9,10] These dehiscences could therefore be due to the presence of gelatin, colistin, or their combination. Although gelatin cannot be excluded as a cause of dehiscence, it is perhaps a less likely culprit as previous studies have not shown dehiscence when gelatin is implanted in the oral and maxillofacial region, though these studies are not extensive.…”
Section: Discussionmentioning
confidence: 99%
“…[7,8] The porosity of these constructs was generated by using a carboxymethylcellulose or gelatin hydrogel as a porogen, and the resulting porosity allowed for greater cumulative release of antibiotic. [7][8][9][10] In these studies, colistin, a polypeptide antibiotic, was incorporated into either gelatin or PLGA microparticles. Colistin was selected due to its efficacy against Acinetobacter baumannii, a commonly multi-drug resistant bacterial strain that has been observed to have increased incidence of infection in traumatic combat wounds [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…24 Sclafani et al demonstrated that biomaterials exposed to bacteria at the time of implantation are more vulnerable to infection than implants inoculated 14 days after implantation, and resistance to infection correlated with histologic evidence of fibrovascular ingrowth into the material implants. 25 However, since porosity may also confer the benefits of improved tissue attachment and fibrovascular ingrowth compared to solid PMMA, 26 efforts should be made to balance tissue integration and infection prevention for tissue engineering applications such as formation of induced membranes. Although one infection did occur in a treated group in this study, infection was significantly mitigated compared to the control group, demonstrating that the controlled release of antibiotics through a porous space maintainer was successful in preventing infection in the majority of cases.…”
Section: Discussionmentioning
confidence: 99%
“…27 Spicer et al mixed polymethylmethacrylate (PMMA) bone cement with carboxymethylcellulose porogen to yield a porous space maintainer that polymerized in situ within a rabbit mandibular defect. 81 Soft tissue healing was observed 12 weeks post-implantation, and inflammatory responses were not exacerbated relative to that of solid PMMA space maintainers.…”
Section: Bone Tissue Engineeringmentioning
confidence: 90%